Measurement of social sustainability indicators in Guilan architecture - Mehran Mehrdoust Shahrestani; Ali Asgharzadeh; Hamzeh Golamalizadeh (تحقیقات کاربردی علوم جغرافیایی)
Among the dimensions of sustainable development, social sustainability is recognized as one of the main dimensions that is most in line with the dimensions of people's lives. The main purpose of this study is to evaluate and evaluate the indicators of social sustainability derived from the global goals of sustainable development (SDGs) in people's lives and its feedback in the geographical architecture of Gilan region. The method of evaluating the rank of the options of this research is Vikor technique and the research method is descriptive-survey and the statistical population studied in this research is the members of 6 groups related to the research subject including: villages of 16 cities of Gilan province Local architects, the Gilan General Directorate of Housing and Natural Resources and Forestry, and non-governmental organizations (NGOs) love the environment, among which the selection of a sample community was made possible by non-probable sampling. Findings show that "social justice" with the highest value of sustainability indicators (0.083) has the highest priority and "social progress and welfare" with (0.034) have the lowest priority and among 6 The social stability index, the two indicators of correlation and responsible consumption, and the average production have been evaluated and are of no importance to the groups related to the architecture of the Guilan region.